Treasure island - Hill, David A. (Helbling Readers)
Book and CD When the terrible pirate Bill Bones dies, young Jim Hawkins is left with the key to a fortune: the long-lost map of Treasure Island. Jim sets off on an incredible adventure with his trusted friends to find the hidden treasure. They do not realize that their crew is made up of pirates and their leader is the most infamous and cruel pirate of them all... Long John Silver. Will Jim and his friends outwit the pirates and get the treasure